Gemstones and sustainable development: Perspectives and trends in mining, processing and trade of precious stones. Issue 4 (November 2019) - Cartier, Laurent E.
Highlights: The majority of coloured gemstones worldwide are mined by artisanal miners. The coloured gemstone sector is poorly researched. There are over a hundred different gemstone varieties and more than fifty producing countries. This special section provides an insight into the sector and overcomes some important research gaps. Abstract: Gemstones have been mined and traded since pre-history, and today represent a complex global industry which is poorly researched. The multitude of gemstone varieties and producing countries for gemstones makes any such research a challenging undertaking. This article introduces a special section that brings together a range of papers that provide an insight into the gemstone sector and some of the different issues in mining, processing and trading stages of gemstones. Sustainable development considerations are also addressed as these are becoming increasingly important in the gemstone and jewellery industry, especially as ethical certification schemes are being designed and put in place. Finally, this article provides a brief overview of the papers included in the special section.